Solution of Dynamic Economic Load Dispatch (DELD) Problem With Valve Point Loading effects and Ramp rate limits Using PSO - G. Sreenivasan (Institute of Advanced Engineering and Science, 2011)
Dynamic economic load dispatch (DELD) is one of the major operational decisions in power system operation and control. It is a Dynamic problem due to dynamic nature of Power system and the large variation of load demand. This absolute problem is normally solved by discretisation of the entire dispatch period into a number of small time intervals over which the load is assumed to be constant and the system is considered to be in temporal steady state. This paper presents particle swarm optimization technique to solve the DELD problem for the determination of the global or near global optimum dispatch solution. To illustrate the effectiveness of the proposed approach, three test systems consisting of 5,10 and 15 generating units, with incorporation of load balance constraints, operating limits, valve point loading, ramp constraints and network lossesare considered and tested. The comparison of numerical results demonstrate the performance and applicability of the proposed method. Keywords: Dynamic economic load dispatch (DELD), Particle Swarm Optimization, Valve - point loading effect, Ramp Rate Limits.DOI:http://dx.doi.org/10.11591/ijece.v1i1.60